2019
DOI: 10.1101/661587
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular characterization of the stress network in the human brain

Abstract: The biological mechanisms underlying inter-individual differences in human stress reactivity remain poorly understood. We aimed to identify the molecular underpinning of neural stress sensitivity.Linking mRNA expression data from the Allen Human Brain Atlas to task-based fMRI revealed 261 differentially expressed genes in brain regions differentially activated by stress in individuals with low or high stress sensitivity. These genes are associated with stress-related psychiatric disorders (e.g. schizophrenia a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 83 publications
(58 reference statements)
0
1
0
Order By: Relevance
“…Despite investigating very different phenomena, these studies reported similar sets of significant GO categories, most frequently implicating categories related to metabolic, neuronal, and generic biological and behavioral processes. The most reported GO category in our survey was 'chemical synaptic transmission' (GO:000726), which has been reported in 15 human analyses from 10 different studies (21,26,32,(69)(70)(71)(72)(73)(74)(75) and four different mouse analyses from three different studies ( organization of human resting-state functional connectivity (21), human adolescent cortical shrinkage and myelination (26), and tract-traced structural connectivity in the mouse brain (17). Some other commonly reported categories include 'potassium ion transmembrane transport' (22,26,32,74,77,78), 'learning or memory' (15,74,75,79,80), and 'electron transport chain' (18,19,23,26,74)…”
Section: Diverse Phenotypes In the Literature Are Enriched For Similamentioning
confidence: 70%
“…Despite investigating very different phenomena, these studies reported similar sets of significant GO categories, most frequently implicating categories related to metabolic, neuronal, and generic biological and behavioral processes. The most reported GO category in our survey was 'chemical synaptic transmission' (GO:000726), which has been reported in 15 human analyses from 10 different studies (21,26,32,(69)(70)(71)(72)(73)(74)(75) and four different mouse analyses from three different studies ( organization of human resting-state functional connectivity (21), human adolescent cortical shrinkage and myelination (26), and tract-traced structural connectivity in the mouse brain (17). Some other commonly reported categories include 'potassium ion transmembrane transport' (22,26,32,74,77,78), 'learning or memory' (15,74,75,79,80), and 'electron transport chain' (18,19,23,26,74)…”
Section: Diverse Phenotypes In the Literature Are Enriched For Similamentioning
confidence: 70%